2011
DOI: 10.1155/2011/928497
|View full text |Cite
|
Sign up to set email alerts
|

Corticotrophin-Releasing Hormone Type 1 Receptor Gene (CRHR1) Variants Predict Posttraumatic Stress Disorder Onset and Course in Pediatric Injury Patients

Abstract: Abstract. Posttraumatic stress disorder (PTSD) is a common and disabling anxiety disorder that may occur in the aftermath of exposure to potentially traumatic life events. PTSD is moderately heritable, but few specific molecular variants accounting for this heritability have been identified. Genes regulating the hypothalamic-pituitary-adrenal (HPA) axis, such as corticotrophinreleasing hormone type 1 receptor gene (CRHR1), have been implicated in traumatic-stress related phenotypes but have yet to be studied i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
63
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 37 publications
3
63
1
Order By: Relevance
“…We also compiled a list of genes that have been reported in the literature to be significantly associated with PTSD, either showing a main effect for the genetic marker, and/or a significant GxE interaction (Amstadter et al, 2009(Amstadter et al, , 2011Binder et al, 2008;Boscarino et al, 2011;Cao et al, 2013;Comings et al, 1996;Dragan and Oniszczenko, 2009;Gillespie et al, 2013;Goenjian et al, 2012;Grabe et al, 2009;Guffanti et al, 2013;Hauer et al, 2011;Kolassa et al, 2010;Logue et al, 2013a,b;Lyons et al, 2013;Mellman et al, 2009;Nelson et al, 2009;Ressler et al, 2011;Segman et al, 2002;Solovieff et al, 2014;Voisey et al, 2010;Wilker et al, 2013;Xie et al, 2013). Since most studies were performed in subjects of either European or African descent, we used these specific ancestry groups for comparison with MRS. We found that most of the 25 candidate genes showed nominally significant associations in MRS for at least one of the SNPs tested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also compiled a list of genes that have been reported in the literature to be significantly associated with PTSD, either showing a main effect for the genetic marker, and/or a significant GxE interaction (Amstadter et al, 2009(Amstadter et al, , 2011Binder et al, 2008;Boscarino et al, 2011;Cao et al, 2013;Comings et al, 1996;Dragan and Oniszczenko, 2009;Gillespie et al, 2013;Goenjian et al, 2012;Grabe et al, 2009;Guffanti et al, 2013;Hauer et al, 2011;Kolassa et al, 2010;Logue et al, 2013a,b;Lyons et al, 2013;Mellman et al, 2009;Nelson et al, 2009;Ressler et al, 2011;Segman et al, 2002;Solovieff et al, 2014;Voisey et al, 2010;Wilker et al, 2013;Xie et al, 2013). Since most studies were performed in subjects of either European or African descent, we used these specific ancestry groups for comparison with MRS. We found that most of the 25 candidate genes showed nominally significant associations in MRS for at least one of the SNPs tested.…”
Section: Discussionmentioning
confidence: 99%
“…Most research has focused on: (1) the hypothalamic-pituitary-adrenal (HPA) axis, (2) the ascending brainstem locus coeruleus noradrenergic system, and (3) the limbic amygdalar frontal pathway mediating fear processing. Among the over 25 PTSD candidate genes currently reported (Amstadter et al, 2009(Amstadter et al, , 2011Binder et al, 2008;Boscarino et al, 2011;Cao et al, 2013;Comings et al, 1996;Dragan and Oniszczenko, 2009;Gillespie et al, 2013;Goenjian et al, 2012;Grabe et al, 2009;Guffanti et al, 2013;Hauer et al, 2011;Kolassa et al, 2010;Logue et al, 2013a,b;Lyons et al, 2013;Mellman et al, 2009;Nelson et al, 2009;Ressler et al, 2011;Segman et al, 2002;Solovieff et al, 2014;Voisey et al, 2010;Wilker et al, 2013;Xie et al, 2013), promising findings include associations of PTSD symptoms with the serotonin transporter gene (SERT, SLC6A4) (Xie et al, 2009), which is linked to depression and anxiety disorders, as well as differential acquisition of conditioned fear and increased amygdala excitability in humans. In addition, FKBP5, a co-chaperone of the glucocorticoid receptor involved in the HPA axis, has a significant interaction with severity of child abuse in the prediction of adult PTSD symptoms, indicating a gene by environment (GxE) interaction (Binder et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, targeted association studies were conducted to test whether CRHR1 polymorphisms -mainly rs7209436, rs110402, and rs242924, forming a haplotype where the TAT combination conveys disease -influence the risk for stress-related disorders like post-traumatic-stress disorder (PTSD; 13,14 ) and depression [15][16][17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…B. Amstadter, Nugent, & Koenen, 2009; Koenen, 2007); however, CRH genes are seemingly particularly consequential (Baker et al, 2005; Smoller et al, 2005; Tyrka et al, 2009; van Gaalen, Stenzel-Poore, Holsboer, & Steckler, 2002). Of candidate gene studies of PTSD to date, few have examined genes influencing the HPA axis (Bachmann et al, 2005; Binder et al, 2008), with one prior study examining a CRH gene (A. B Amstadter et al, 2011).…”
Section: Introductionmentioning
confidence: 99%